Indigo Carmine Hemodynamic Studies to Treat Vasoplegia Induced by Compound 48/80 in a Swine Model of Anaphylaxis - Albuquerque,Agnes Afrodite S (2022)
Abstract Introduction: There are many reasons to believe that the nitric oxide/guanosine 3’5’ - cyclic monophosphate (or NO/cGMP) pathway on vasoplegic states is underestimated. To study indigo carmine (IC) as an alternative to methylene blue was the investigation rationale. Methods: The IC (3mg/kg intravenous infusion) study protocol included five experimental groups; 1) Control group — saline was injected at 0 and 10 minutes; 2) IC group — IC was injected at 0 and saline at 10 minutes; 3) compound 48/80 (C48/80) group — C48/80 was injected at 0 minute and saline at 10 minutes; 4) C48/80 + IC group — C48/80 was injected at 0 minute and IC at 10 minutes; and 5) IC + C48/80 group — IC was injected at 0 minute and C48/80 at 10 minutes. The studies were carried out by registering and measuring hemodynamic and blood gasometric parameters, including continuous cardiac output. Results: 1) The effects of the drugs (IC and C48/80) were more evident in the first 20 minutes of recording; 2) hypotensive responses were more pronounced in the C48/80 groups; 3) IC isolated or applied before C48/80 caused transient pulmonary hypertension; and 4) after the first 20 minutes, the pressure responses showed stability with apparent hypotension more pronounced in the C48/80 groups. Clinical observations showed significant hemodynamic instability and catastrophic anaphylactic reactions (agitation, pulmonary hypertension, severe bronchospasm, urticaria, high-intensity cyanosis, violent gastric hypersecretion, and ascites). Conclusion: A global results analysis showed differences between groups only in the first 20 minutes of the experiments.